Rational Empiricism : The idealist view of (elementary) physics - Solari, Hernán Gustavo; Natiello, Mario Alberto (Centre for Mathematical Sciences, Lund University, 2025)
This book attempts to reconstruct elementary physics in full compliance with reason, thus continuing the work of philosophers (experimental and mathematical) throughout the centuries. The unabridged Newton's mechanics is recovered, Gauss intuitions about relational electromagnetism are developed and completed and Schrödingers undulatory quantum theory is reproposed, unifying all three theories in one formulation, and connecting with psychological and philosophical works, as well as with the historical context. Out of the development of the three fundamental theories in physics spawns a discussion about how general scientific theories evolve, as well as the decisive role of reason highlighted through its "marvelous self-correcting property" (Peirce).